2015
DOI: 10.1111/iji.12231
|View full text |Cite
|
Sign up to set email alerts
|

Profile of killer cell immunoglobulin‐like receptor and its human leucocyte antigen ligands in dengue‐infected patients from Western India

Abstract: Killer cell immunoglobulin-like receptors (KIRs) regulate the activation of natural killer cells (NKs). Qualitative and quantitative differences in the type and the number of KIRs expressed on NK cells affect its activation which would influence the outcome of the disease. In this study, 114 hospitalized cases of dengue [82 dengue fever (DF) and 32 dengue haemorrhagic fever (DHF) cases] and 104 healthy controls (HC) without no known history of hospitalization for dengue-like illness were investigated for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…For this reason, the difference in KIR2DL3 expression should also be interpreted with caution. Although KIRs have been implicated in dengue disease severity (47)(48)(49), whether the expression of KIRs on CD8 + T cells has any functional role in anti-DENV immunity warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the difference in KIR2DL3 expression should also be interpreted with caution. Although KIRs have been implicated in dengue disease severity (47)(48)(49), whether the expression of KIRs on CD8 + T cells has any functional role in anti-DENV immunity warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, there is genetic evidence that supports the role of KIRs in DENV infections as well. In studies done in Gabon, Brazil and in Western India, a difference in the frequencies of KIR genes such as KIR3DL1, KIR3DS1, KIR2DS1, KIR2DS5 and KIR2DL5 was found in patients with dengue compared with healthy controls . Furthermore, the analysis in one study found a possible protective effect against dengue fever in individuals with the AA genotype.…”
Section: Killer Cell Immunoglobulin‐like Receptor Interactions With Denvmentioning
confidence: 97%
“…In parallel, genetic evidence supports the role of KIRs in flavivirus infection. In studies performed in Gabon, Brazil and Western India, a difference in the frequencies of KIR genes was found in patients infected with DENV, as compared with healthy controls [33,79,80]. Mechanistically, KIR molecules interact with DENV peptides presented on HLA molecules.…”
Section: Nk Cell Responses Following Arbovirus Infectionmentioning
confidence: 99%